(untitled) (ENTHYMEMA, 2025)
According to Bakhtin, chronotope is a device involved in structuring the plot, as an organizational center around which the sense of the text is condensed through a intersection between topology and chronology. Furthermore, spatiotemporality can also determine the genre of the literary work itself. This is particularly evident in Zero K (2016) by Don DeLillo, a novel divided into two distinct sections set in two antinomic chrotonopes, one of transcendence and one of immanence. Consequently, the text is similarly divided into two different narrative genres, one related to the utopian and catastrophic novel and the other to the urban and political novel. The protagonist, Jeffrey Lockhart, is a sort of chronotopic Wandersmann who walks through both textual sections mixing the two worlds represented and the relative space-times and genres. This paper aims to investigate the chronotopic architecture of Zero K through a close reading capable of highlighting the hybridization between different spaces and times and thus between different literary genres.